2003
DOI: 10.1076/neur.9.1.70.14374
|View full text |Cite
|
Sign up to set email alerts
|

Basal Ganglia Lesions and the Theory of Fronto-Subcortical Loops: Neuropsychological Findings in Two Patients with Left Caudate Lesions

Abstract: Basal ganglia lesions have a high prevalence for associated behavioural impairments. However, the exact pattern of cognitive impairments and its relationship to individual basal ganglia lesion have rarely been investigated by means of a detailed neuropsychological and lesion study. Furthermore, different mechanisms have been proposed as relevant for the observed cognitive deficits; among these, the hypothesis of fronto-subcortical loops (Alexander et al., 1986) has made predictions regarding the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 75 publications
3
63
1
2
Order By: Relevance
“…In fact, if the intrinsic difficulty of the tasks were influencing the level of performance, one should expect that patients with other neurological conditions should also fail in this or in other similar tests. Rather, it is now well-established that different degenerative diseases show characteristic impairment profiles which follow particular lesional/degeneration patterns, such as in the case of Alzheimer disease (Carlomagno et al, 1999;Delazer, Karner, Proell & Benke, 2006;Helpern, McMilla, Moore, Dennis & Grossman, 2003;Martini, Domahs, Benke & Delazer, 2003;Zamarian et al, 2007b), Parkinson disease and other basal ganglia dysfunctions (Benke, Delazer, Bartha & Auer, 2003;Delazer et al, 2004;Tamura et al, 2003;Zamarian et al, 2006), semantic dementia (Cappelletti, Butterworth & Kopelman, 2001, 2012, amyothrophic lateral sclerosis (Palmieri et al, 2013), and genetic defects (e.g., Bertella et al, 2005;Semenza et al, 2008;Semenza et al, 2012). Each degenerative disease seems to affect aspects of number processing and calculation in a distinct way.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, if the intrinsic difficulty of the tasks were influencing the level of performance, one should expect that patients with other neurological conditions should also fail in this or in other similar tests. Rather, it is now well-established that different degenerative diseases show characteristic impairment profiles which follow particular lesional/degeneration patterns, such as in the case of Alzheimer disease (Carlomagno et al, 1999;Delazer, Karner, Proell & Benke, 2006;Helpern, McMilla, Moore, Dennis & Grossman, 2003;Martini, Domahs, Benke & Delazer, 2003;Zamarian et al, 2007b), Parkinson disease and other basal ganglia dysfunctions (Benke, Delazer, Bartha & Auer, 2003;Delazer et al, 2004;Tamura et al, 2003;Zamarian et al, 2006), semantic dementia (Cappelletti, Butterworth & Kopelman, 2001, 2012, amyothrophic lateral sclerosis (Palmieri et al, 2013), and genetic defects (e.g., Bertella et al, 2005;Semenza et al, 2008;Semenza et al, 2012). Each degenerative disease seems to affect aspects of number processing and calculation in a distinct way.…”
Section: Discussionmentioning
confidence: 99%
“…Benke et al [15] discussed case reports of two patients, PJ (male, aged 56) and AS (female, aged 58), who had suffered from spontaneous left basal ganglia haematoma. In PJ the caudate nucleus was mainly affected, whilst in AS mainly the globus pallidus and putamen were affected with relatively minor damage to the caudate nucleus.…”
Section: Case Reportsmentioning
confidence: 99%
“…In most studies it is suggested that, there is an evidence of basal ganglia dysfunction which can be showed by morphologic and functional neuroimaging techniques 4 . Basal ganglia dysfunction can also present with cognitive impairment, characterized mainly by executive dysfunction 5 . So, it may be considered that degeneration of frontostriatal loops could lead not only to motor and behavioural changes but also to cognitive abnormalities in SC 6 .…”
mentioning
confidence: 99%